Bean common mosaic : Screening for disease resistance - Morales, Francisco José (International Center for Tropical Agriculture, 1989)
Methods used to identify BCMV are described in terms of symptomatology (common mosaic, black root); transmission (seed, insect, manual); responses of differential bean cv. (mosaic, systemic or local necrosis, local lesions, immunity); cytology (light and electron microscopy); purification and serology (double immunodiffusion test, enzyme-linked immunosorbent assay, immunosorbent electron microscopy); and BCMV characterization. Procedures in genetic improvement for resistance to BCMV include sources of resistance, incorporation of BCMV resistance to susceptible bean cv., multiple resistance to mosaic and necrosis- inducing BCMV strains, evaluation of germplasm for resistance, incorporation of the dominant necrosis (I) gene, screening for multiple resistance, and backcrossing. Production of BCMV-free seed, and seed germination and serological tests are presented. A flow chart outlining a general purification procedure for most BCMV strains is appended. Color photographs are included. (CIAT)